Metal corrosion monitoring with acoustic emission technique. (November 2015) - Li, B. Y.; Zhang, W.
Abstract : By establishing an effective experimental platform, the acoustic emission signals during the corrosion process of metal were collected. The characteristics of the signals were consistent with the analysis. This indicates that the corrosion process of metal can produce acoustic emission signals, and acoustic emission technique can be used for monitoring metal corrosion and evaluating the damage of corrosion.